Comparison of the biological principles underlying the action of monoclonal antibody (mAb) and decoy receptor anti-VEGF agents – on the example of ranibizumab (anti-VEGF-A mAb) and aflibercept (decoy VEGFR1-2 receptor) - Golik, Paweł; Tońska, Katarzyna (Klinika Oczna / Acta Ophthalmologica Polonica, 2012)
Current state-of-the-art anti-angiogenic therapies target the VEGF pathway, which is the main essential signaling pathway for angiogenesis, including pathological angiogenesis in cancer and eye disease. Ranibizumab (Lucentis) and VEGF-Trap (aflibercept) represent two different approaches to inhibiting angiogenesis by targeting VEGF family signaling. The former is a relatively short monoclonal antibody fragment, which binds VEGF-A on the basis of antigen recognition by the variable region of an antibody, while aflibercept is not an monoclonal antibody, but a decoy receptor, binding VEGF-A on the basis of the molecular interaction between the ligand (VEGF) and its cognate cellular receptor (VEGFR-1 and VEGFR-2). VEGF-Trap has therefore a broader specificity, recognizing and binding VEGF-B and PlGF in addition to VEGF-A, following the specificity of VEGFR-1 and VEGFR-2. This broader specificity is considered as beneficial in cancer treatment and could be also beneficial in treatment of nAMD, this claim should, however, be backed by clinical studies. The presence of an Fc fragment in VEGF-Trap is also an important difference; even though this fragment does not participate in the recognition of the target molecule, it can influence the biological properties of the fusion protein. The relative merits of both approaches will become clear only after long-term laboratory and clinical testing, as their biological activity is also likely to differ. Given the clear differences in the mechanism of target molecule recognition, biochemical and biophysical properties (including molecular weight) and specificity, they cannot be considered as equivalent, unless extensive long-term clinical studies prove otherwise.